2020
DOI: 10.1111/jgh.15058
|View full text |Cite
|
Sign up to set email alerts
|

Use of hepatitis B virus core‐related antigen to evaluate natural history of chronic hepatitis B

Abstract: Background and Aim: Hepatitis B core-related antigen (HBcrAg) has been shown to correlate with various viral markers in chronic hepatitis B, but its role in defining natural history is not well studied. We aimed to investigate the use of HBcrAg to define different phases of chronic hepatitis B. Methods: Stored residual serum samples from longitudinal cohorts of chronic hepatitis B patients in Hong Kong and Japan were studied. Viral markers were measured in three serial serum samples for each patient. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…In retrospective studies from Asia and Europe, the median serum HBcrAg level was 8.4 to 8.8 log U/mL in patients with HBeAg-positive chronic infection, 7.9 to 8.5 log U/mL in those with HBeAg-positive chronic hepatitis, 4.5 to 4.9 log U/mL in those with HBeAg-negative chronic hepatitis, and 2.0 to 3.1 log U/mL in those with HBeAg-negative chronic infection. [17][18][19] In general, serum HBcrAg level is correlated with serum HBV DNA and HBsAg levels. A meta-analysis of 74 studies involving 5,591 HBV-infected patients found that a HBcrAg cut-off of 5.3 log U/mL was optimum for identifying patients with HBV DNA !200,000 IU/mL (sensitivity: 91.8%; specificity: 90.5%), while HBcrAg cut-off at 3.6 log U/mL was useful for identifying patients with HBV DNA !2,000 IU/mL (sensitivity: 85.2%; specificity: 84.7%).…”
Section: Clinical Implications Of a Role Of Hbcrag In The Natural History Of Chronic Hepatitis Bmentioning
confidence: 99%
See 3 more Smart Citations
“…In retrospective studies from Asia and Europe, the median serum HBcrAg level was 8.4 to 8.8 log U/mL in patients with HBeAg-positive chronic infection, 7.9 to 8.5 log U/mL in those with HBeAg-positive chronic hepatitis, 4.5 to 4.9 log U/mL in those with HBeAg-negative chronic hepatitis, and 2.0 to 3.1 log U/mL in those with HBeAg-negative chronic infection. [17][18][19] In general, serum HBcrAg level is correlated with serum HBV DNA and HBsAg levels. A meta-analysis of 74 studies involving 5,591 HBV-infected patients found that a HBcrAg cut-off of 5.3 log U/mL was optimum for identifying patients with HBV DNA !200,000 IU/mL (sensitivity: 91.8%; specificity: 90.5%), while HBcrAg cut-off at 3.6 log U/mL was useful for identifying patients with HBV DNA !2,000 IU/mL (sensitivity: 85.2%; specificity: 84.7%).…”
Section: Clinical Implications Of a Role Of Hbcrag In The Natural History Of Chronic Hepatitis Bmentioning
confidence: 99%
“…6.0 log U/mL had 97.3% sensitivity and 93.4% specificity for differentiating HBeAgpositive from HBeAg-negative samples. 19 No viral marker can predict HBeAg seroconversion 1 to 2 years ahead. 19 However, HBcrAg tends to drop significantly before HBeAg seroconversion, which suggests a possible role of serial monitoring of HBcrAg in clinical practice.…”
Section: Clinical Implications Of a Role Of Hbcrag In The Natural History Of Chronic Hepatitis Bmentioning
confidence: 99%
See 2 more Smart Citations
“…HBcrAg can still be detected in patients with undetectable serum HBV DNA or loss of HBsAg, and reduction in HBcrAg level is strongly associated with favorable outcomes. This novel marker appears to correlate with serum HBV DNA and intrahepatic cccDNA copy number (Chan et al, 2020 (online ahead of print)). Unlike HBsAg and HBeAg, the use of HBcrAg as a marker is still largely confined to the research setting.…”
Section: Hbv Infectionmentioning
confidence: 99%